2017
DOI: 10.3389/fcimb.2017.00216
|View full text |Cite
|
Sign up to set email alerts
|

Protease Inhibitors in Tick Saliva: The Role of Serpins and Cystatins in Tick-host-Pathogen Interaction

Abstract: The publication of the first tick sialome (salivary gland transcriptome) heralded a new era of research of tick protease inhibitors, which represent important constituents of the proteins secreted via tick saliva into the host. Three major groups of protease inhibitors are secreted into saliva: Kunitz inhibitors, serpins, and cystatins. Kunitz inhibitors are anti-hemostatic agents and tens of proteins with one or more Kunitz domains are known to block host coagulation and/or platelet aggregation. Serpins and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
101
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(105 citation statements)
references
References 174 publications
(245 reference statements)
3
101
0
1
Order By: Relevance
“…Serpins are evolutionarily conserved and also widely distributed in arthropods . Large numbers of protease inhibitors were found to be expressed in the tick salivary glands, including Cystatin, Serpin and Kunitz‐like family . cDNAs encoding serpin‐like proteins have now been cloned from several tick species, including Ixodes scapularis , Ixodes ricinus , Boophilus microplus , Haemaphysalis longicornis and Rhipicephalus appendiculatus .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Serpins are evolutionarily conserved and also widely distributed in arthropods . Large numbers of protease inhibitors were found to be expressed in the tick salivary glands, including Cystatin, Serpin and Kunitz‐like family . cDNAs encoding serpin‐like proteins have now been cloned from several tick species, including Ixodes scapularis , Ixodes ricinus , Boophilus microplus , Haemaphysalis longicornis and Rhipicephalus appendiculatus .…”
Section: Introductionmentioning
confidence: 99%
“…cDNAs encoding serpin‐like proteins have now been cloned from several tick species, including Ixodes scapularis , Ixodes ricinus , Boophilus microplus , Haemaphysalis longicornis and Rhipicephalus appendiculatus . Some tick serpins have been shown to be associated with counter defense against anti‐tick responses in the host, such as inflammation, complement activation, platelet aggregation, and blood clotting . In other studies, tick serpins are suggested as being important in tick feeding physiology, as significant reductions in feeding efficiency had been observed in ticks that fed on animals immunized with recombinant tick serpins .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, approximately 20 tick cystatins, all belonging to family types 1 and 2, have been reported [48]. Their functions include immunomodulatory (host or itself), Borrelia and Anaplasma phagocytophilum infections, and tick feeding, attachment, and hatching.…”
Section: Discussionmentioning
confidence: 99%
“…These complex processes allow the ticks to remain attached for a prolonged period and compensate for different host defense mechanisms and requirements of the tick feeding cycle. Tick salivary molecules can be grouped into major categories based on their function, such as lipocalins (acting as kratagonists of biogenic amines and prostanoids), metalloproteases (having fibrinolytic activity), Kunitz-domain containing peptides (having putative sodium channel blocking or anticlotting activities), basic tail polypeptides (a unique protein family having anti-thrombin or plasminogen-activating activities), the salp-15 family (having immunosuppressive activity), the Isac family (having anticomplement activity), glycine-rich peptides (immunogenic components of the tick cement) (Francischetti et al, 2009;Blisnick et al, 2017;Chmelar et al, 2017;Šimo et al, 2017). Interestingly, not all molecules are secreted simultaneously .…”
Section: Introductionmentioning
confidence: 99%